Gestational Toxoplasmosis: an Epidemiological Study - Santos, Bárbara Monique dos (2023)
Gestational toxoplasmosis is the result of the placental transfer of T. gondii to the fetus, which produces a series of serious consequences for the baby The study allowed the registration of 156 cases of gestational toxoplasmosis from 2019 to 2022, 03 participants were excluded, of which: a non-pregnant woman, one male and a 62-year-old woman, totaling a sample of 153 cases participating in the research. The research aimed to understand the epidemiological situation of Toxoplasmosis in Maceió. The research was a quantitative epidemiological study with a descriptive, retrospective approach, using secondary data from the Notifiable Diseases Information System (SINAN - NET), made available by the Municipal Health Department of Maceió. The importance of investigating the epidemiological situation of toxoplasmosis, through morbidity indicators is necessary, due to the complexity of toxoplasmosis and what it can compromise the life of the pregnant woman and the newborn. Concluding in this way that the quality of the information transmitted by the health services and by the professionals that comprise the multidisciplinary health teams for the population will be decisive for the change of behaviors, for the adoption of healthy life habits.